Some Ambiguous Features for Geologic Interpretation - H.D. Tjia (Journal of Mathematical and Fundamental Sciences, 1969)
Abstract. Among geologic features, which do not indicate phenomena claimed by textbooks, are triangular facet developed on steeply inclined dipslopes, sensation of coarseness that does indicate the sense of fault displacement, and orientation of long pebble-axes perpendicular to transport direction, examples of these features are demonstrated.Ichtisar. Penulis telah mendjumpai beberapa gedjala geologi jang mempunjai arti berlainan dari pada jang biasa dikemukakan oleh "tectbooks"; antara lain ditemukan facet-facet segitiga jang terbentuk pada dipslope tjuram, kesan kasar sepandjang slickendside jang menundjukkan arah gerak sesar, dan sumbu-sumbu memandjang dari batuguling jang berkedudukan tegak terhadap arah pengangkutan.